Briket Sabut Kelapa (Cocos nucifera L.) sebagai Bahan Bakar Alternatif Berbasis Sumber Daya Alam Lokal/Coconut (Cocos nucifera L.) Coir Briquettes as an Alternative Fuel Based on Local Natural Resources - Yelfira Sari; Putri Ade Rahma Yulis (Lambung Mangkurat University Press, 2023)
One of the practical and efficient products of biomass processing is briquettes. Briquettes are densified products in the form of cubic, prism, or cylindrical shapes. One of the biomass produced from abundant agricultural waste in Riau Province is coconut coir. This is because Riau Province is one of the largest coconut-producing regions in Indonesia. The utilization of coconut coir waste is currently still limited to crafts, fuel, and planting media. This study aims to produce briquettes from a waste of old coconut coir and young coconut coir with the stages of the research process including cleaning, drying, grinding, adding adhesive, and densification. The resulting briquettes were then subjected to laboratory tests to determine the physical characteristics of the briquettes based on SNI No. 1/6235/2000 and structural characteristics using SEM and TG/DTG. The results showed that laboratory tests for old coconut coir briquettes and young coconut coir based on water content were 28.11% and 29.72%; based on ash content are 1.59% and 2.21%; based on the carbon content are 25.10% and 24.94%, and the heating value is 3019.54 cal/g and 3137.03 cal/g. For SEM analysis, the surface morphology of the briquettes looked smooth and there was no fragmentation indicating that the biomass was perfectly bonded with the binder used. Meanwhile, in the TG/DTG analysis, the results showed that there had been a mass decrease of around 90% for old coconut coir briquettes and 78% for young coconut coir briquettes at a temperature of around 450oC